(untitled) (Nepal Journal of Epidemiology, 2017)
It has been said that practice makes progress and progress leads to perfection, and we have made immense progress by the formation and revision of retraction policies and this has understandably led to the publication of more authentic literature in recent times. However, multiple hurdles still do exist and by virtue of authentic studies we hope to overcome them with the eventual goal of a world of publication free of misconduct.